2023
DOI: 10.3390/cancers15184456
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B Expression in the Tumor Microenvironment as a Prognostic Biomarker for Patients with Triple-Negative Breast Cancer

Kimihisa Mizoguchi,
Hitomi Kawaji,
Masaya Kai
et al.

Abstract: Tumor-infiltrating lymphocytes in the tumor microenvironment are important in the treatment of triple-negative breast cancer (TNBC). Cytotoxic T cells produce cytokines and cytotoxic factors, such as perforin and granzyme, which induce apoptosis by damaging target cells. To identify biomarkers of these cells, we investigated granzyme B (GZMB) in the tumor microenvironment as a biomarker of treatment response and prognosis in 230 patients with primary TNBC who underwent surgery without preoperative chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In studies related to GZMB, it was observed that in the PD-L1-positive group, Kaplan–Meier analysis revealed better recurrence-free survival (RFS) and OS in triple-negative breast cancer (TNBC) patients with high expression of GZMB (defined as ≥ 1% tumor-infiltrating lymphocytes (TILs) positive). Both RFS and OS were significantly prolonged in patients with high GZMB expression (RFS: P = 0.0220, OS: P = 0.0254) (Mizoguchi et al 2023 ). Multivariable Cox analysis also indicated better OS in patients with high expressions of PD-L1 and GZMB (hazard ratio: 0.25 (95% CI: 0.07–0.88), P = 0.03), suggesting that GZMB is a useful prognostic biomarker for PD-L1-positive TNBC patients (Mizoguchi et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies related to GZMB, it was observed that in the PD-L1-positive group, Kaplan–Meier analysis revealed better recurrence-free survival (RFS) and OS in triple-negative breast cancer (TNBC) patients with high expression of GZMB (defined as ≥ 1% tumor-infiltrating lymphocytes (TILs) positive). Both RFS and OS were significantly prolonged in patients with high GZMB expression (RFS: P = 0.0220, OS: P = 0.0254) (Mizoguchi et al 2023 ). Multivariable Cox analysis also indicated better OS in patients with high expressions of PD-L1 and GZMB (hazard ratio: 0.25 (95% CI: 0.07–0.88), P = 0.03), suggesting that GZMB is a useful prognostic biomarker for PD-L1-positive TNBC patients (Mizoguchi et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both RFS and OS were significantly prolonged in patients with high GZMB expression (RFS: P = 0.0220, OS: P = 0.0254) (Mizoguchi et al 2023 ). Multivariable Cox analysis also indicated better OS in patients with high expressions of PD-L1 and GZMB (hazard ratio: 0.25 (95% CI: 0.07–0.88), P = 0.03), suggesting that GZMB is a useful prognostic biomarker for PD-L1-positive TNBC patients (Mizoguchi et al 2023 ). Additionally, a study found that high expression of GZMK in advanced melanoma significantly improved patients' PFS and OS (PFS: P = 0.04, OS: P = 0.01) (Wu et al 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that high GZMB is associated with the increased cytotoxic activity of tumor‐infiltrating lymphocytes (TILs) and improved disease‐free survival (DFS) and OS in multiple cancer types. 62 , 63 However, GZMB expression alone or coupled with markers like PD‐L1 can variably affect both recurrence‐free survival (RFS) and OS. 62 , 64 , 65 Our study supports these contradictory data by demonstrating that high GZMB expression is linked with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“… 62 , 63 However, GZMB expression alone or coupled with markers like PD‐L1 can variably affect both recurrence‐free survival (RFS) and OS. 62 , 64 , 65 Our study supports these contradictory data by demonstrating that high GZMB expression is linked with poor survival. It implies that the impact of cytotoxic activity may vary depending on the cancer type and immunological context.…”
Section: Discussionmentioning
confidence: 99%